A rare case of proximal arm neurofibroma causing ulnar nerve compression: successful surgical intervention and recovery - Mohammed K., Najeeb; Mammu, Sharafuddeen; B., Deepak; Chacko V. H., Nidhin (International Journal of Research in Orthopaedics, 2024)
Compressive neuropathy of the ulnar nerve due to a neurofibroma above the elbow is extremely rare, with few cases reported worldwide. A young male presented with a progressively enlarging swelling and increasing pain in the right upper arm. Over time, the patient developed symptoms indicative of ulnar nerve compression, including numbness, tingling, and weakness in the hand and forearm. Physical examination and diagnostic imaging revealed the presence of a neurofibroma compressing the ulnar nerve above the elbow. The patient also exhibited generalized features consistent with neurofibromatosis, such as multiple café-au-lait spots and cutaneous neurofibromas. Given the severity of the symptoms and the confirmed diagnosis, the patient underwent surgical excision of the neurofibroma along with neurolysis to decompress the ulnar nerve. The surgical intervention aimed to relieve pain and improve sensory and motor function. The surgical procedure was successful, resulting in significant pain relief and marked improvement in sensory and motor functions. Postoperatively, the patient reported substantial symptomatic relief and regained functional use of the affected limb. This case underscores the importance of considering rare causes of ulnar nerve compression, such as neurofibromas, particularly in patients with underlying neurofibromatosis. It also highlights the effectiveness of surgical removal and nerve decompression in resolving symptoms and restoring function in such complex cases.